Water Quality Status of Situ Tlajung Hilir Assessed by The STORET Method - Mia Azizah; Eva Muzdalifah; Dian Arrisujaya (Universitas Nusa Bangsa, 2026)
Situ Tlajung Hilir is a small lake in Wanaherang Village (Gunung Putri, Bogor Regency) that supports irrigation, recreational fishing, and small-scale aquaculture for the surrounding community. After reports of severe pollution in late 2021, when blackened and malodorous water accompanied by fish kills was linked to domestic and industrial discharges, its present condition warranted re-assessment. This study evaluated the lake’s water-quality status using the STORET method against the Class II criteria of Government Regulation No. 22 of 2021. Samples drawn from three representative points (Points 1–3) on a single sampling occasion (19 March 2023) were examined for temperature, TDS, TSS, pH, COD, BOD, DO, total phosphate, sulphate, dissolved cadmium and lead, and fecal coliform, following the relevant Indonesian National Standards (SNI) and Standard Methods (23rd ed.) through gravimetric, titrimetric, spectrophotometric, ICP-OES, and Most Probable Number techniques. Averaged over the three points, the physical indicators and the dissolved metals stayed within Class II limits, whereas COD (27.35 mg/L), BOD (5.43 mg/L), DO (4.2 mg/L), total phosphate (0.10975 mg/L), and fecal coliform (2000 MPN/100 mL) each breached their thresholds. Summing the penalty scores produced a STORET value of –90, classifying the lake as Class D (heavily polluted), with organic and microbial loading from domestic and adjacent land-use activities as the dominant drivers.